FORECASTING THE IMPACT OF CARBON TAX ON EMISSIONS REDUCTION IN VIET NAM - Dinh Thi Thanh Binh; Le Thi Thu Hang; Cao Thi Nhat Le (International Journal of Application on Economics and Business, 2024)
Carbon taxes have been proposed or applied in many countries and regions around the world to reduce greenhouse gas emissions (GHG). In this paper, the author uses the Stretton model to estimate the impact of a carbon tax in the implementation of the goal of reducing net emissions to 0% by 2050. The results show that the Carbon tax has a positive impact in helping Vietnam reduce greenhouse gas emissions, specifically with scenario 1, the Carbon tax helps reduce CO2 by 9.728% by 2030 and up to 20.28% in 2050 compared to the BAU scenario; with the scenario 2, the emissions will be reduced by 15.619% in 2030 and 20.67% in 2050 compared to the BAU scenario, however, if the tax increase on coal is equal to the tax rate on natural gas, the emission reduction will be 33.206% in 2050. From the research results, the authors also propose a number of recommendations and solutions to help Vietnam successfully apply a Carbon tax to reduce emissions towards the net emission target of equal to 0 by 2050 as committed at the COP 26 in 2021.